Legal protection of personal data in e-commerce transactions towards a safe and trusted digital economy - Wahdah, Nurwafiq Al; Dantye, Femylia (ProBisnis : Jurnal Manajemen, 2024)
This research aims to analyze the legal protection of personal data in e-commerce transactions, which is an important aspect in maintaining security and trust in the digital economy. The author employs a normative legal research method. The results of the research indicate that in an era where electronic commerce increasingly dominates business activities, the protection of personal data becomes a primary foundation to ensure consumer trust and the sustainable development of the digital economy. Through appropriate policies and regulations, states and relevant stakeholders can establish a legal framework that effectively governs the collection, use, and protection of personal data in the context of e-commerce. These measures help create a safe and trusted business environment where consumers feel comfortable conducting online transactions without concerns about the misuse of their personal data. Thus, legal protection of personal data in e-commerce transactions not only secures individuals' interests in safeguarding their privacy but also supports national economic growth through the establishment of a secure and trustworthy digital economy.